Improving feedback on junior doctors' prescribing errors: mixed-methods evaluation of a quality improvement project. Issue 3 (4th April 2016) - Reynolds, Matthew; Jheeta, Seetal; Benn, Jonathan; Sanghera, Inderjit; Jacklin, Ann; Ingle, Digby; Franklin, Bryony Dean
Abstract : Background: Prescribing errors occur in up to 15% of UK inpatient medication orders. However, junior doctors report insufficient feedback on errors. A barrier preventing feedback is that individual prescribers often cannot be clearly identified on prescribing documentation. Aim: To reduce prescribing errors in a UK hospital by improving feedback on prescribing errors. Interventions: We developed three linked interventions using plan–do–study–act cycles: (1) name stamps for junior doctors who were encouraged to stamp or write their name clearly when prescribing; (2) principles of effective feedback to support pharmacists to provide feedback to doctors on individual prescribing errors and (3) fortnightly prescribing advice emails that addressed a common and/or serious error. Implementation and evaluation: Interventions were introduced at one hospital site in August 2013 with a second acting as control. Process measures included the percentage of inpatient medication orders for which junior doctors stated their name. Outcome measures were junior doctors' and pharmacists' perceptions of current feedback provision (evaluated using quantitative pre-questionnaires and post-questionnaires and qualitative focus groups) and the prevalence of erroneous medication orders written by junior doctors between August and December 2013. Results: The percentage of medication orders for which junior doctors stated their name increased from about 10% to 50%. Questionnaire responses revealed a significant improvement in pharmacists' perceptions but no significant change for doctors. Focus group findings suggested increased doctor engagement with safe prescribing. Interrupted time series analysis showed no difference in weekly prescribing error rates between baseline and intervention periods, compared with the control site. Conclusion: Findings suggest improved experiences around feedback. However, attempts to produce a measurable reduction in prescribing errors are likely to need a multifaceted approach of which feedback should form part.